From Policy to Practice: The Uganda Climate-Smart Agriculture Multistakeholder Platform Annual Review 2025 - Barungi, Julian; Okonya, Joshua; Anyango, Prossy; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
A four-day Annual forum 2025 organized by the Uganda Climate Smart Agriculture (CSA) Multistakeholder Platform (UG-CSA-MSP) was held in Uganda on 16th -19th September 2025. The event brought together 84 stakeholders implementing CSA initiatives (34 females, 50 males) from Government Ministries, Agencies and departments, International and national research institutes, UN agencies, farmer organizations, private companies, civil society organizations and universities who reflected on progress of implementation of CSA initiatives in the country, identified challenges to adoption of CSA technologies and innovations, and proposed strategies for scaling, monitoring and reporting on climate actions in the agricultural sector.